Illicit alcohol consumption and its associated factors among patrons in Zambia: a cross-sectional analytical study - Zyambo, Cosmas; Phiri, Masauso Moses; Zulu, Richard; Mukupa, Musawa; Mabanti, Kumbulani; Matenga, Tulani Francis L.; Rizzo, Angela; Hainze, Anna; Ogwell, Ahmed; Menda, Dhally; Goma, Fastone; Achoki, Tom (Frontiers in Public Health, 2025)
IntroductionIllicit alcohol consumption is prevalent globally, particularly in low- and middle-income countries where formal regulatory systems are weak or less enforced. Consumption of illicit alcohol has serious consequences, both immediate and long-term.ObjectiveTo examine the socio-demographic and behavioral factors associated with the consumption of illicit alcohol among the patrons in selected urban and peri-urban areas in Zambia.MethodsThis was a cross-sectional study. Illicit alcohol consumption status, socio-demographics and behavioral factors were assessed. Adjusted multivariable logistic regression was used to obtain odds ratios (AOR) at a 95% confidence interval (CI).ResultsOf the 416 patrons who participated, 71.2% consumed illicit alcohol (Men, 75.3% vs. women 54.7%). More than 66.8% reported needing a drink first thing in the morning, 50.2% have had problems with friends due to alcohol and 19% did indicate having visited the hospital due to a drinking problem. In multivariable analysis, factors significantly associated with decreased odds of illicit alcohol consumption were females (AOR) 0.38 (95% CI: 0.20–0.73, p = 0.003), Ndola city (AOR = 0.28, 95% CI: 0.12–0.62, p = 0.002), drinking pattern of 2–3 days a month (AOR: 0.19, 95% CI: 0.06–0.53, p = 0.002) and incomes above K10,000 (AOR: 0.40, 95% CI: 0.19–0.85, p = 0.017). The inability to stop drinking (AOR = 2.86, 95% CI: 1.22–6.69, p = 0.016) had an increased odds of illicit alcohol consumption.ConclusionOur findings underscore the high prevalence of illicit alcohol consumption among the patrons. Addressing illicit alcohol consumption requires a multifaceted set of interventions that consider the various factors contributing to alcohol misuse, and focuses on prevention, education, support, and community engagement.